The Morse Telegraph Alphabet - Hawkins, N. (Nehemiah) (New Catechism of Electricity: A Practical Treatise, 1896)
Text and illustration from page 479 of the 1896 volume New Catechism of Electricity detailing the Morse code alphabet and numerals used to communicate via telegraph.
Keywords: Communication; Communication and technology; Electrical engineering; Electricity; Telecommunication; Telegraph; Cipher and telegraph codes; Morse code